The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ie900857m
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Actual Object Size Distribution from Direct Imaging

Abstract: Direct imaging is a technique commonly used in the study of particle, bubble, and droplet size distribution in a dynamic system. Objects such as particles, bubbles, and droplets can be present at various distances from the imaging device when images are captured. Hence, the location of the object will need to be known in order to determine the actual size of an individual object. However, the location of the object cannot be determined from a single image. A single calibration scale defined at the focusing pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…1(a), the image processing was started by cropping the raw camera image to contain only the circular photobioreactor portion. A pre-developed image analysis algorithm (Hossain et al, 2009) was then utilized to convert the cropped image from RGB space into grayscale based on the equation Lee, 2003, 2006):…”
Section: Light Distribution Measurementmentioning
confidence: 99%
“…1(a), the image processing was started by cropping the raw camera image to contain only the circular photobioreactor portion. A pre-developed image analysis algorithm (Hossain et al, 2009) was then utilized to convert the cropped image from RGB space into grayscale based on the equation Lee, 2003, 2006):…”
Section: Light Distribution Measurementmentioning
confidence: 99%
“…From the measured nanotube length by AFM, it was found that the length approximately follows the lognormal distribution. Indeed, lognormal distribution is widely accepted to describe the distribution of size/length of particles [35][36][37]. A lognormal distribution is solely determined by two parameters: the mean (µ) and standard deviation (σ) of the natural logarithm of the random variable (i.e.…”
Section: Chemometric Methodsmentioning
confidence: 99%
“…To the best of our knowledge, many researchers have carried out this study thoroughly using numerous techniques including Doppler anemometry techniques [8], tomographic techniques [9], invasive probe techniques, and direct imaging techniques [10]. Additionally, image analysis with advanced mathematical methods, regarded as a normal practice, is gaining importance for object identification [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The bubble size distribution (BSD) of the discrete phases in multiphase systems such as the BSD of bubbles in gas-liquid or gas-liquid-solid systems is significant for the operation of the specific applications. The knowledge of BSD can enhance the understanding of mixing and heat and mass transfer properties for design and scale-up of the operations [10]. The direct imaging technique has been a common technique for BSD measurement in multiphase systems [22,23].…”
Section: Introductionmentioning
confidence: 99%